Nordic statements on apartheid - Nordiska Afrikainstitutet (Nordiska Afrikainstitutet, 1977)
Contents: Statements made in plenary meetings of the General Assembly by: 1. The Minister for Foreign Affairs of Finland -- 2. The representative of Norway -- 3. The representative of Denmark -- 4. The representative of Sweden -- 5. The representative of Iceland -- Statements in the Security Council by: Mr. Olof Palme, Sweden -- Ambassador Anders Thunborg, Sweden -- Statements at the United Nations Conference in Maputo by: Mr. Ola Ullsten, Sweden -- Mr. Olof Palme, Sweden